A prospective trial of vaccine to prevent hepatitis B virus reactivation after hematopoietic stem cell transplantation - Nishikawa, Koji (Bone Marrow Transplant, 2020)
Hepatitis B virus (HBV) reactivation reportedly occurs frequently after hematopoietic stem cell transplantation (HSCT) in resolved HBV-infected patients. Here, 50 patients with resolved HBV infections and scheduled to undergo HSCT were enrolled; all subjects were vaccinated with three doses of hepatitis B vaccine 12 months after HSCT and the incidence of HBV reactivation was monitored. The patients’ characteristics were: median age, 61 (34–72) years; male/female, 27/19; allogeneic/autologous, 40/6; bone marrow/peripheral blood stem cells/cord blood, 26/16/4. Of the 46 patients who underwent HSCT, 19 were excluded and did not make it to vaccination due to relapse of underlying disease, HBV reactivation within 12 months of HSCT, or transfer of patients. The remaining 27 were vaccinated 12 months after HSCT and monitored for 2 years. Six showed HBV reactivation, with a 2-year cumulative reactivation incidence of 22.2%; the same incidence was 27.3% only in allogeneic HSCT patients. Factors associated with HBV reactivation included the discontinuation of immunosuppressants (P = 0.0379) and baseline titers of antibody against hepatitis B surface antigen (P = 0.004). HBV reactivation with vaccination following HSCT could occur despite maintenance of serum anti-HBs at more than protective levels.